Dahrendorf as champion of a liberal society–border crossings between political practice and sociopolitical theory - Kühne, Olaf (SocietàMutamentoPolitica, 2019)
Ralf Dahrendorf is internationally known for his work on role and conflict theory but rather less so for his large body of writing on liberalism, civil society, and the constitutional concept of freedom, little of which has been translated into English or other languages. Focusing on Dahrendorf’s German-language publications, the present article addresses this gap. In developing his concept of liberalism and its implications for practical politics, Dahrendorf centrally invokes his theory of roles—the roles the individual is called upon to play—and strongly defends the individual against the behavioral expectations of society. And from his fundamental thesis of the productivity of regulated conflicts he concludes that such conflicts are fundamental to a free society: a society in which errors can always be revised. In his later publications, the social question of maximizing individual opportunities in life (or what he called life chances) became more central. Even after his death in 2009, Dahrendorf’s ideas have continued to influence discussion about the development of a liberal society.